2(5+2n)=-2(n-3)

Simple and best practice solution for 2(5+2n)=-2(n-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5+2n)=-2(n-3) equation:



2(5+2n)=-2(n-3)
We move all terms to the left:
2(5+2n)-(-2(n-3))=0
We add all the numbers together, and all the variables
2(2n+5)-(-2(n-3))=0
We multiply parentheses
4n-(-2(n-3))+10=0
We calculate terms in parentheses: -(-2(n-3)), so:
-2(n-3)
We multiply parentheses
-2n+6
Back to the equation:
-(-2n+6)
We get rid of parentheses
4n+2n-6+10=0
We add all the numbers together, and all the variables
6n+4=0
We move all terms containing n to the left, all other terms to the right
6n=-4
n=-4/6
n=-2/3

See similar equations:

| 100=16-2x | | 2x-x^2=8÷9 | | 9+2d=4(7−3d) | | 5h=h(4+1 | | |5x-15|=10 | | 3(3x+4)=7(x+3) | | 5m-2(m+2=-(2m+15) | | 2(x-1/2)=4(x=1/4 | | 34+c=71 | | 7+5x=5x=1/2(14+10x) | | -22+5x=-38+x | | 8c-2c^2=14 | | 6=7(2+10c) | | -2x+3-x=3x+15 | | -5x-20=8-(x+4) | | x=x1.0765+645.34 | | 5–z=z-1 | | 45/22=100/x | | -5(2x+5)+9x=-32 | | 21+2n=-4(n+9) | | 80x-32=16(5x-2) | | 1÷2(w-8)=1÷4(w+6) | | 44x+50=44x+20 | | -150=6(-9m+2) | | 3(x+4)=2x-(-2) | | 29-9x=12+8x | | w-6=5w+10 | | 6.2g+2=4.2g+8. | | (X-2)=-5(3-x)-1 | | A+4c=8 | | 16x+10=3(4x-14) | | (2x+42)+(x-18)+x=180 |

Equations solver categories